Decision Making Processes for a Pregnant Woman Admitted to the Accident and Emergency Department Requiring Emergency Diagnostic X-ray – A Case Study - S. Ismanto (ASEAN Journal on Science and Technology for Development, 2015)
The objective of this study is to apply the decision-making processes for a pregnant woman who was involved in a motor vehicle accident and admitted to a private middle-class hospital in the capital of Indonesia requiring radiologic X-ray examination.  It also aims to examine and evaluate the patient who was in her 20th week of gestation in order to provide her with the best emergency care, diagnostic investigations and treatments.The descriptive, normative and prescriptive models of decision-making are demonstrated. The descriptive model used intuition, while the normative model used decision trees as decision options and lastly the prescriptive decision used the information processing theory (IPT) to decide on the best emergency care, diagnostic investigations and treatments for the patient. The IPT dominated the decision-making process; hence an X-ray examination was done that was safe for the fetus and the childbearing mother. Decision option was not used since the patient was in pain and could not understand much of the procedure that was explained.  Intuition helped in the decision-making in order to ensure safe and effective practice.